Al-Mawardi’s Concept of Justice - Aladdin, Ghassan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
A return to heritage and its evocation is not just an attempt to assess its elements, question its soul, and judge it positively or negatively. It is above all for the production of components and events of that heritage in the context of a new understanding, established on the belief that the Islamic heritage is only a practice of political experiences controlled by the priorities of interest and benefits among parties each of which claims to defend the legitimacy of what is adopted and believed in through depending mainly on the religious text. In other words, this research aims to read the experience of (Al-Mawardi) in politics via new concepts and entries which were absent for a long time as a result of its disappearance behind a sacred religious text, which favors every reading that inspires its spirit. In brief, the research attempts to observe the concept of justice as viewed by Al-Mawardi in his discussion of the duties of the ruler and his ministers towards citizens from one side, and the duties of citizens towards them from the other side, hoping to seek the most important articulations of that concept as Al-Mawardi tried to establish.